Tying all the offerings to the goddess - Mumbai Archive Project Team (Jio Institute, 2024)
Once all the offerings have been placed in the cloth, it is twisted, folded, and tied around the womb of the effigy. Several such pieces of cloth are tied around the effigy, each donated by a groups or families.